Distance deterrence effect and intergenerational similarity in the field-of-study choices of Finnish university students - Tuomo Suhonen (European Regional Science Association (ERSA), 2012)
Numerous studies have found that school proximity and parents' educational background affect individuals' educational attainment, while less evidence has been presented on the role of these factors in the choice of university field of study. Especially, in a geographically vast and scarcely populated country, such as Finland, distances may have an important effect on these choices, as the variety of fields and majors in students' nearest universities vary considerably across locations. Parents' influence on the field of study choice could, then again, arise from inherited or learned career preferences that lead individuals to graduate from the same fields as their parents did. In addition, field of study choices could be affected by the same-sex effect: men may prefer fields chosen by their fathers, while women may prefer fields chosen by their mothers. By using a register-based data set provided by Statistics Finland, this paper analyses the field of study choices of Finnish university students who graduated from high school between 1991 and 1996. The study's emphasis is on analyzing to what extent the individuals' field of study choices are associated with the location of high school and the resulting shortest distances to enroll in different fields, and to what extent individuals choose the same field as their father or mother did. The econometric analysis relies on multinomial discrete choices models and the use of controls, e.g., for pre-university grades in first language and math. The estimation results suggest that an increase in the distance to enroll in a field significantly decreases the probability of choosing that field, which applies both for men and women. The evidence of parental effects is more mixed: whereas men's probability to self-select into a field is, on average, strongly associated with father having graduated from that field, no significant average parental effects are found for women. Furthermore, the results from a mixed logit analysis suggest that, while the effect of distance to enroll is roughly constant across individuals, the parental effects exhibit considerable individual heterogeneity. These results indicate that policies aiming to transform multidisciplinary universities into more specialized institutions could have unwanted side-effects, as increasing distances to enroll constraint individuals' field of study choices.
Keywords: 330